Performance of MiMo-OFDM Systems in Rayleigh Channel - Eni Dwi Wardihani (JAICT, 2019)
Along with the development of wireless communication makes the increasing demand for obtaining quality services and better range, bandwidth-efficient and reliable system. OFDM is a multicarrier transmission technique to overcome multipath fading, which may result in intersymbol interference (ISI). On the other hand there is the antenna system with the use of multiple antennas at the transmitter and receiver that can also be overcome multipath fading,ie Multiple Input Multiple Output (MIMO) to increase channel capacity and diversity gain. MIMO techniques used in this Final adaldah Space Time Block Code. Simulation aims to simulate and analyze the MIMO OFDM technique using space-time block code against the influence of the number of subcarriers and influence user speed in AWGN channel and Rayleigh. The simulation results based on the number of subcarriers in AWGN channel, the best performance is obtained by subcarrier number 256. With BPSK and QPSK modulation obtained BER = 6 10-4 when SNR 4 dB. Simulation based on Rayleigh channel obtained when BER = 9.7 10-5 with BPSK modulation. Based on the comparison of the greater frequency doppler given doppler frequency, resulting in BER generated even greater, because the state of the canal will be getting worse.